(untitled) (Journal of Universal Excellence, 2026)
Research Question (RQ): Is there a correlation between hero culture and silo mentality? Which are the potential dysfunctionalities that arise from this "hero-silos" paradigm? Purpose: We conducted a systematic review of scientific literature in order to gain sights into the "hero-silos" paradigm. Method: A systematic review of scientific literature was conducted in the following academic search engines: Google Scholar, Scopus, JSTOR, Springer Nature, ScienceDirect, SAGE, Wiley Online Library, Web of Science, and Base (Open Access), as well as Google, ResearchGate. Results: We detected some emerging patterns that shed light on the correlation between hero culture and silo mentality. We stress that this correlation must be further investigated, as well as conceptualizing the term “hero” in a proper way. Organization: The research sheds light on how the dynamic hero-silo resembles an iceberg, giving managers tools to make the problem visible and to examine the issue in organizational culture from another perspective. Society: The findings evidence that the hero-silo mentality is an unconscious phenomenon influencing the work environment negatively. The visibility of this problem helps to increase productivity as well as to elevate the engagement/motivation of the employees. Originality: The originality of the research is reflected on the initially detected potential correlation among hero culture and silo mentality, as well as dysfunctionalities that arise from this linkage, which have to be furtherly researched. Limitations / further research: We found a limitation in open access to published academic literature, that could enrich the research. The divergence in the definition of “hero” has been also limitation for conducting research. We suggest further quantitative research on the correlation of hero culture and silo mentality in organizations.